The Influence of Return on Equity and Debt to Equity Ratio on Company Value at PT. Astra International Tbk Listed on the Indonesia Stock Exchange (IDX) in 2016-2023 - Sipa Yeni (Formosa Journal of Sustainable Research, 2024)
This study aims to examine how the effect Return on Equity and Debt to Equity Ratio on firm value of PT. Astra Internationa Tbk listed on the indonesia stock exchange from 2016-2023 with the sample selectioan method using the purposive sampling method. The data used are the company’s annual financial statements that have been publised on IDX and the data analysis technique is multiple linear regression analysis using the SPSS 25. The results show that simultaneously Return on Equity and Debt to Equity Ratio have a significant effect on firm value, partially Return on Equity yield has a significant positive effect to firm value, partially Debt to Equity Ratio yield has a significant positive effect to firm value.